Corporate Social Responsibility PT Kereta Api Indonesia (Persero) dalam Penguatan Program Sahabat Difabel - Wulandari, Zulfa Amania Asfani; Mukarom, Zaenal; Faizin, Barzan (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2022)
This research aims to find out the process carried out by CSR PT KAI (Persero) in running a program organized through difable friends, using the four steps of public relations and using a qualitative approach with descriptive methods. Researchers used data collection techniques through in-depth interviews, observation, and documentation. The results showed that the results of this study indicate that PT Kereta Api (Persero)'s Corporate Social Responsibility in strengthening the difable friend program is considered effective. Running a program for the welfare of people with disabilities is an effort to build the company's image in the eyes of the community by providing services both morally and materially. Thus, through the difable friend program, the public perception of PT KAI (Persero) as a company that takes sides and is friendly to people with disabilities.